Elektabilitas Calon Kepala Desa Wayame Dalam Pemelihan Kepala Desa Wayame Kota Ambon - Rukoyah, Rukoyah (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2023)
Research carried out in Wayame Village to measure the eligibility of candidates for the village chief in the election to the homogeneous village in Ambon City. The problem at the site of the research is the low public participation as well as the weak public accountability in the village of Wayame. The research method is qualitatively descriptive by conducting in-depth interviews with the informant in person. As far as the research is concerned, the Wayame village community's political participation rate is very good to have seven candidates for the village chief. High political participation because the community wants a village leader who has integrity and a good leadership record. Research findings that people are very rational in determining the choice of wayame village heads who have experience and level of education can affect the selection of candidates who advance the election to wayame.